An immune system-inspired byte permutation function to improve confusion performance of round transformation in symmetric encryption scheme. - Ariffin, Suriyani; Mahmod, Ramlan; Jaafar, Azmi; Rezal, Muhammad; Ariffin, Kamel (Springer, 2012)
In data encryption, the security of the algorithm is measured based on Shannon’s confusion and diffusion properties. This paper will proposed the Levinthal’s paradox and protein structure essential computation elements on the basis of diversity property of immune systems that satisfy with confusion property of symmetric encryption scheme. This paper measures and analysis the confusion property of the permutation function of a block cipher using the correlation coefficient statistical analysis to identify whether it satisfies Shannon’s confusion property. From the analysis carried out, the permutation function block cipher increased the performance of the confusion property, hence, indicating a high non-linear relationship between plain text and cipher text in symmetric encryption scheme.